Tuning Biological Nutrient Removal Plants. - Hartley, Ken (Iwa Publishing, 2014)
Tuning Biological Nutrient Removal Plants increases interest in tuning to enhance both performance and capacity, to provide insight into typical plant operating characteristics, and to stimulate operators' interest in studying the behaviour of their own plants. The book focuses on understanding of plant behavioural characteristics so that optimum performance can be achieved and maintained. Tuning Biological Nutrient Removal Plants is carefully organized to cover: influent and effluent characteristics; process fundamentals; individual process characteristics; overall plant characteristics; the evolutionary operation approach to tuning. The approach is practical and the use of mathematics is kept to a minimum and information is supplied in graphical and tabular form. Real operating data from a wide range of plant experiences is included. The book draws on the generosity of many Australian plant owners in permitting their plant data to be incorporated. Not all process types are covered but the tuning principles expounded are universally applicable. The capacity and performance capabilities of a plant are not fixed; both are amenable to on-going enhancement through systematic and enthusiastic effort. The book will help to set new benchmarks in plant operation. Tuning Biological Nutrient Removal Plants is a valuable resource for sewage treatment operations and operations support personnel, sewage process design engineers operating authorities, consultants, contractors, operators of industrial wastewater treatment plants and sewage treatment lecturers in chemical engineering departments and other training organisations.